Influência da temperatura sobre o processo de decomposição dos esgotos domésticos em lagoas facultativas - Klüsener, João Júlio (2006)
The increase of the urbanization added by little investments in sanitation is one of the main problems of public health in Brazil. One of the challenges of sanitation is to improve efficient treatment systems with low operational and implantation costs. This work analyzed the influence of the temperature upon the process of wastwater stabilization in a system of facultative ponds with the intention of contributing for the improvement of designing facultative ponds. It was used data of twenty years of sewer treatment plant of the Rosário do Sul city in Rio Grande do Sul. The bulletins report parameters of air temperature, sewer temperature, pH, dissolved oxygen, settleable solids, suspended solids, sulfides, and biological oxygen demand. As results, the correlations between the air temperature and the sewer temperature were established for three points on the system: entrance of the system; effluent of primary pond; effluent of secondary pond. It was verified that the parameters of DO, pH, and sulfides increased with the increase of temperature. The suspended sólids removal eficiency increase with the elevation of temperature, however it was not verified increase or decrease of settleable solids and BOD removal according to the variation of the temperature. It was also possible to stablish equations Ls = f(T), that relate the BOD surface loading that can be applied to a facultative pond with respect to the air temperature. These equations were the first ones based on data collected in Rio Grande do Sul.